2015
DOI: 10.1371/journal.pone.0126976
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium pseudocatenulatum CECT 7765 Reduces Obesity-Associated Inflammation by Restoring the Lymphocyte-Macrophage Balance and Gut Microbiota Structure in High-Fat Diet-Fed Mice

Abstract: Background/ObjectivesThe role of intestinal dysbiosis in obesity-associated systemic inflammation via the cross-talk with peripheral tissues is under debate. Our objective was to decipher the mechanisms by which intervention in the gut ecosystem with a specific Bifidobacterium strain reduces systemic inflammation and improves metabolic dysfunction in obese high-fat diet (HFD) fed mice.MethodsAdult male wild-type C57BL-6 mice were fed either a standard or HFD, supplemented with placebo or Bifidobacterium pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(155 citation statements)
references
References 49 publications
7
147
1
Order By: Relevance
“…The mechanism is at least partly related to the amelioration of the diet-induced endotoxemia and inflammation in the gut, liver, and in adipose tissue [45, 50, 51], and the deconjugation of bile acids [52], which influences the host’s lipid metabolism and energy expenditure [23]. B. pseudocatenulatum has been shown to cause changes in the expression of hepatic genes involved in lipid metabolism [53].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism is at least partly related to the amelioration of the diet-induced endotoxemia and inflammation in the gut, liver, and in adipose tissue [45, 50, 51], and the deconjugation of bile acids [52], which influences the host’s lipid metabolism and energy expenditure [23]. B. pseudocatenulatum has been shown to cause changes in the expression of hepatic genes involved in lipid metabolism [53].…”
Section: Discussionmentioning
confidence: 99%
“…Because the microbiota is rapidly altered by diet and the consumption of a HFD is known to cause obesity , it has been suggested that diet‐induced alterations in microbiota could contribute to the pathogenesis of obesity. To identify potentially beneficial and detrimental bacteria for obesity development, we review the HFD‐induced effects on common parameters related to obesity and on the rodent microbiota . A number of significant correlations between the human or rodent microbiota and several common parameters related to obesity have been reported (Table ) .…”
Section: Intestinal Microbiota Composition Associated With Diet‐inducmentioning
confidence: 99%
“…However, the complexity of the human microbiome may make it difficult to deconvolute the many cross-reactive peptides that could be driving this link. Associations between specific gut microbes and disease [100] may make it possible to narrow down the possibilities, although it seems unlikely that a single gut microbe will be the culprit.…”
Section:  Autoimmune Disease and The Gut Microbiomementioning
confidence: 99%